Postprandial lipemic and inflammatory responses to high-fat meals: a review of the roles of acute and chronic exercise. Issue 1 (December 2016) - Teeman, Colby; Kurti, Stephanie; Cull, Brooke; Emerson, Sam; Haub, Mark; Rosenkranz, Sara
Abstract Postprandial lipemia is an independent risk factor for development of cardiovascular disease. Postprandial inflammation following the prolonged elevation of triglycerides occurring subsequent to ingestion of high-fat meals, provides a likely explanation for increased disease risk. Substantial evidence has shown that acute exercise is an effective modality for attenuation of postprandial lipemia following a high-fat meal. However, much of the evidence pertaining to exercise intensity, duration, and overall energy expenditure for reducing postprandial lipemia is inconsistent. The effects of these different exercise variables on postprandial inflammation is largely unknown. Long-term, frequent exercise, however, appears to effectively reduce systemic inflammation, especially in at-risk or diseased individuals. With regard to an acute postprandial response, without a recent bout of exercise, high levels of chronic exercise do not appear to reduce postprandial lipemia. This review summarizes the current literature on postprandial and inflammatory responses to high-fat meals, and the roles that both acute and chronic exercise play. This review may be valuable for health professionals who wish to provide evidence-based, pragmatic advice for reducing postprandial lipemia and cardiovascular disease risk for their patients. A brief review of proposed mechanisms explaining how high-fat meals may result in pro-inflammatory and pro-atherosclerotic environments is also included.